Chromosomal Abnormalities - Aşkın Çelik, Tülay; Dey, Subrata (IntechOpen, 2020)
Chromosomes are vital components of genetic material, and, as such, distruption or changes to the structure of chromosomes can result in different health problems and deficits. This book explains chromosomal abnomalities and their effects on living organisms, including humans and plants. Classical and molecular cytogenetics techniques have a considerable number of potential applications, especially in clinical trials and biomedical diagnosis, making them a strong and insightful complement to other molecular and genomic approaches. Chapters cover topics including Down syndrome, fetal ultrasounds, acute myeloid leukemia, and Phelan-McDermid syndrome, among others.